Global justice and development - Culp, Julian 1983- (Palgrave Macmillan, 2014)
"What, if any, are the demands of global distributive justice? How, if at all, does global distributive justice affect our understanding of social development and the moral justifiability of international development policies? Global Justice and Development answers the first question by arguing that the demands of global distributive justice ought to be determined in a reasonably democratic manner. Accordingly, the primary demand of global distributive justice is to establish the political and socioeconomic conditions necessary for reasonably democratic arrangements. In response to the second question, this book makes the case that such a procedural view of global distributive justice challenges all substantive normative conceptions of social development that focus on particular outcomes rather than on proper political procedures. It also justifies why this procedural view of global distributive justice morally justifies certain democracy-enhancing international development policies as requirements of justice rather than as humanitarian duties of assistance. "..